Pengaruh Promosi dan Kualitas Pelayanan terhadap Minat Menabung Nasabah pada Bank Muamalat Kab. Kolaka : Studi Kasus pada Bank Muamalat Kab. Kolaka - Fitri Kumalasari; Suwarto Suwarto; Yul Fitri (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to determine: (1) The Effect of Promotion on Customer Saving Interest at Bank Muamalat Kab. Kolaka (2) The Effect of Service Quality on Customer Saving Interest at Bank Muamalat Kab. Kolaka This research uses an approach with Quantitative methods, Data collection in this study using Observation, Literature Study and Questionnaire Distribution. The population of this research is customers and prospective customers who are in Kolaka Regency. While the sample of this study amounted to 98 people. Testing this research instrument using the Validity Test and Reliability Test with SPSS 25.0. The data analysis technique used in this study is the measurement model test (outer model) and structural model testing (inner model) with Smart PLS 4.0.Based on the results of the study, it is known that there is a positive and significant influence between the Promotion variable on Saving Interest, which is indicated by a t-statistic value of 6,100 with a P-Value of 0.000 and the Service Quality variable also has a positive and significant effect on Brand loyalty, which is indicated by a t-statistic value of 2,042 with a P-Value of 0.021.